2012
DOI: 10.1016/j.jimonfin.2012.01.015
|View full text |Cite
|
Sign up to set email alerts
|

International portfolio diversification: Currency, industry and country effects revisited

Abstract: We examine the relative importance of country, industry, world market and currency risk factors for international stock returns. Our approach focuses on testing the mean-variance efficiency of the various factor portfolios. An unconditional analysis does not detect significant differences between country, industry and world portfolios, nor any role for currency risk factors. However, when we allow expected returns, volatilities and correlations to vary over time, we find that equity returns are mainly driven b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 54 publications
2
26
0
1
Order By: Relevance
“…When the currency risk of the benchmark assets is 24 Only a handful of studies test the diversification benefits from simple FX excess returns (long forward positions), e.g. Glen andJorion (1993), de Roon, Nijman, andWerker (2003), Eiling, Gerard, Hillion, and de Roon (2009), and most recently Campbell, de Medeiros, and Viceira (2010).…”
Section: B Mean-variance Efficiency Testsmentioning
confidence: 99%
“…When the currency risk of the benchmark assets is 24 Only a handful of studies test the diversification benefits from simple FX excess returns (long forward positions), e.g. Glen andJorion (1993), de Roon, Nijman, andWerker (2003), Eiling, Gerard, Hillion, and de Roon (2009), and most recently Campbell, de Medeiros, and Viceira (2010).…”
Section: B Mean-variance Efficiency Testsmentioning
confidence: 99%
“…In contrast to our paper, they explore the implication of industry only in a regional framework. Similarly, Eiling et al (2012) show that international returns are primarily driven by industry and currency risk factors in the G7 countries only. The key feature is the use of sector-based data.…”
Section: Related Literaturementioning
confidence: 92%
“…Moreover, De Nicolo and Kwast (2002) and Binici et al (2013) documented that return correlations among banks' stocks could be explained by bank-specific factors such as their market shares, the size of their total loan portfolios and the level of their non-performing loans. Further, studies of international markets such as Eiling et al (2012) found that equity returns were mainly driven by global industry and currency risk factors. Chiang et al (2015) and Chiang and Chen (2016) found that conditional correlations of returns in Chinese stock markets and the stock markets of the EU, the US and some Asian countries depended on economic variables, such as the variance of oil price changes, the variance premium of the stock market and implied volatilities.…”
Section: Review Of the Relevant Literaturementioning
confidence: 99%
“…Recently, a growing literature on market efficiency has started to examine the linkages between stock markets, or study the relationship between various risk factors and equity returns/volatility (e.g., Fama and French 1992;Ho et al 2005;Eiling et al 2012;Garcia et al 2015;Vidal-Garcia et al 2016). Some researchers have investigated return comovements across international stocks (Bekaert et al 2009;Bekaert et al 2011;Chiang and Chen 2016).…”
Section: Introductionmentioning
confidence: 99%